Cascade Synthesis of Five‐Membered Lactones using Biomass‐Derived Sugars as Carbon Nucleophiles. Issue 11 (9th May 2016) - Yamaguchi, Sho; Matsuo, Takeaki; Motokura, Ken; Miyaji, Akimitsu; Baba, Toshihide
Abstract: We report the cascade synthesis of five‐membered lactones from a biomass‐derived triose sugar, 1, 3‐dihydroxyacetone, and various aldehydes. This achievement provides a new synthetic strategy to generate a wide range of valuable compounds from a single biomass‐derived sugar. Among several examined Lewis acid catalysts, homogeneous tin chloride catalysts exhibited the best performance to form carbon–carbon bonds. The scope and limitations of the synthesis of five‐membered lactones using aldehyde compounds are investigated. The cascade reaction led to high product selectivity as well as diastereoselectivity, and the mechanism leading to the diastereoselectivity was discussed based on isomerization experiments and density functional theory (DFT) calculations. The present results are expected to support new approaches for the efficient utilization of biomass‐derived sugars. Abstract : Biomass conversion : The cascade synthesis of five‐membered lactones from a biomass‐derived triose sugar, 1, 3‐dihydroxyacetone, and various aldehydes has been reported. The cascade reaction led to high product selectivity as well as diastereoselectivity, and the mechanism explaining the diastereoselectivity was discussed based on isomerization experiments and density functional theory (DFT) calculations.